Performance Evaluation of PV Panel Under Dusty Condition - Abhishek Kumar Tripathi; M. Aruna; Ch.S.N. Murthy (International Journal of Renewable Energy Development, 2017)
The performance of PV panel depends on the incoming sunlight on its surface. The accumulated airborne dust particles on panel surface creates a barrier in the path of sunlight and panel surface, which significantly reduces the amount of solar radiation falling on the panel surface. The present study shows a significant reduction in short circuit current and power output of PV panel due to dust deposition on its surface, whereas the reduction in open circuit voltage is not much prominent. This study has been carried in the field as well as in the laboratory. The reduction in maximum power output of PV panel for both the studies ensures a linear relation with the dust deposition on its surface. In the field study, the reduction in the power output due to 12.86gm of dust deposition on the panel surface was 43.18%, whereas in the laboratory study it was 44.75% due to 11gm of dust depositionArticle History: Received July 10th 2017; Received in revised form Sept 15th 2017x; Accepted 1st Oct 2017; Available onlineHow to Cite This Article: Tripathi, A.K., Aruna, M. and Murthy, Ch.,S.N. (2017). Performance Evaluation of PV Panel Under Dusty Condition. International Journal of Renewable Energy Develeopment, 6(3), 225-233.https://doi.org/10.14710/ijred.6.3.225-233